A Mineral Oil Plant Protection Product Improves Turfgrass Quality of Deficit Irrigated Bermudagrass - Mingying Xiang; Marco Schiavon; Pawel Orlinski; James H. Baird (HortTechnology)
Managing turfgrass in arid and semiarid areas of the southern United States is becoming increasingly challenging due to prolonged drought and diminishing water resources. Turfgrass managers have been seeking products that control pests while promoting drought resistance. CivitasTM Turf Defense is a new petroleum-derived spray oil (PDSO) mixed with green pigment. Like other traditional PDSO products, Civitas is reported to have positive effects on turfgrass pest control and management. However, limited information is available regarding its impact on water conservation in turfgrass. The objective of this study was to evaluate the effects of Civitas on bermudagrass (Cynodon spp.) under deficit irrigation conditions. A 2-year study was conducted in Riverside, CA, USA, to evaluate the effect of Civitas on bermudagrass irrigated at 55% or 65% of reference evapotranspiration (ETo), which represented a 20% or 10% savings in water, respectively. Civitas was applied at 4.5 or 8.5 oz/1000 ft2 every two weeks (2019–20), and 8.5 oz/1000 ft2 every 3 weeks (2019 only), compared with an untreated control. Results show that Civitas improved bermudagrass quality under deficit irrigation at both rates, but the 3-week application interval was less effective compared with the 2-week application interval at either rate. Civitas applied at 8.5 oz/1000 ft2 every 2 weeks resulted in better turfgrass quality than the 4.5 oz/1000 ft2 rate in the first year only. Results suggest that using Civitas on bermudagrass can save up to 20% water while maintaining desirable turf quality.